Plant-based milk microcapsule containing walnut oil and preparation method thereof

By preparing SPI-Cur-NPs powder mixed with walnut oil and maltodextrin, anhydrous trehalose and inulin as wall materials, plant-based milk microcapsules were prepared by spray-drying, the problem of degradation of the quality of nanoemulsion unsaturated oil in the prior art was solved, and high packaging rate, oxidation resistance and long-term stability were achieved.

CN119498410APending Publication Date: 2025-02-25HEFEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411691565.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to develop a plant-based nanoemulsion containing long-chain omega-3 fatty acids and antioxidant capacity that does not affect the quality of unsaturated oils.

Method used

Plant-based milk microcapsules wrapped with walnut oil were prepared by spray drying by spray-drying the SPI-Cur-NPs powder and mixed with walnut oil to form a nanoemulsion, followed by mixed wall system with maltodextrin, anhydrous trehalose and inulin.

Benefits of technology

High packaging rate and oxidation resistance without affecting the quality of unsaturated oil are achieved, which significantly improves the solubility and storage stability of microcapsules and extends the quality retention time of the oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119498410A_ABST
    Figure CN119498410A_ABST
Patent Text Reader

Abstract

The invention provides a plant-based milk microcapsule containing walnut oil and a preparation method of the plant-based milk microcapsule, and relates to the technical field of plant-based milk microcapsules, SPI-Cur-NPs powder is prepared firstly, then emulsion is prepared, the emulsion and walnut oil are prepared into nano-emulsion, finally, the nano-emulsion, maltodextrin (MD), anhydrous trehalose (TA) and inulin (IN) serve as a mixed wall material system, and the plant-based milk microcapsule containing walnut oil is prepared. The plant-based milk microcapsules wrapping the walnut oil are prepared through spray drying, and the preparation method is simple; the composition of the anhydrous trehalose and the maltodextrin can alleviate the fracture formation of particles only containing the maltodextrin, and the prepared microcapsule powder forms a firmer intermolecular hydrogen bond network and an obvious amorphous structure, and enhances the integrity of the wall, thereby reducing the collapse of the particles, and significantly improving the encapsulation rate and solubility; the curcumin and the composite wall material form a compact and uniform coating layer, so that an effective physical barrier is provided, and the microcapsule powder has excellent oxidation stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plant-based milk microcapsules, and particularly relates to plant-based milk microcapsules containing walnut oil and a preparation method thereof. Background Art

[0002] Growing concerns about the global greenhouse effect have intensified the pursuit of alternative protein sources, making plant-based milk substitutes with eco-friendly properties a prominent issue in contemporary food processing. Compared with milk, plant-based substitutes still need to overcome many challenges, including the lack of long-chain omega-3 fatty acids and the insufficient ratio of omega-3 and omega-6 fatty acids. Plant protein-stabilized Pickering nanoemulsions for the delivery of unsaturated oils such as walnut oil can address these nutritional issues by effectively incorporating these beneficial fats. In the research of the prior art, pea protein was used together with flaxseed oil to produce nanoemulsions. These nanoemulsions improved the uniformity of taste while increasing the bioavailability of fat-soluble nutrients in the oil. However, the huge specific surface area of ​​the nanoemulsion may significantly increase the frequency of droplet interactions with oxidants (such as air, metal ions, and ROS), resulting in a decrease in the quality of the delivered unsaturated oil. Therefore, the development of a plant-based nanoemulsion containing long-chain omega-3 fatty acids and antioxidant capacity has become a pressing issue in this research field. Summary of the invention

[0003] In view of this, the present invention provides a plant-based milk microcapsule containing walnut oil without affecting the quality of unsaturated oil.

[0004] It is also necessary to provide a method for preparing plant-based milk microcapsules containing walnut oil.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for preparing plant-based milk microcapsules containing walnut oil comprises the following steps:

[0007] Preparation of SPI-Cur-NPs powder: soy protein isolate was heated in a water bath, then cooled to room temperature, and then curcumin-ethanol solution was added, reacted for 7-9 hours, centrifuged, rotary evaporated, and freeze-dried to obtain SPI-Cur-NPs powder;

[0008] Preparation of nanoemulsion:

[0009] S1: SPI-Cur-NPs powder was dissolved in deionized water, stirred for 2 h, and incubated at 4 °C overnight to obtain SPI emulsion;

[0010] S2: mixing the SPI emulsion and walnut oil in a predetermined volume ratio, and then uniformly obtaining a microemulsion;

[0011] S3: homogenizing the microemulsion to obtain a nanoemulsion;

[0012] Preparation of MD-TA-IN microcapsule powder: The nanoemulsion is mixed and homogenized with an equal volume of a composite wall material solution to obtain a mixture, and the mixture is spray-dried to obtain microcapsule powder.

[0013] Preferably, in the preparation of the SPI-Cur-NPs powder, the concentration of the curcumin-ethanol solution is 4.3-4.7 mg / mL, and the concentration of the solution reaches 50 μmol / L after the curcumin-ethanol solution is added.

[0014] Preferably, in the step S2, the volume ratio of the SPI emulsion to walnut oil is 9:1. The nanoemulsion prepared with this volume ratio has good environmental resistance. Other volume ratios are not acceptable. Other volume ratios cannot guarantee the size of the emulsion before spray drying, resulting in easy aggregation and poor drying effect during hot air drying.

[0015] Preferably, in step S3, the average particle size of the nanoemulsion droplets is 243nm-247nm.

[0016] Preferably, in step S3, the viscosity of the nanoemulsion is below 8.1±0.6 mPa-s.

[0017] Preferably, in the preparation of the MD-TA-IN microcapsule powder, the composite wall material solution is maltodextrin or a 1:1:1 mixture of maltodextrin, anhydrous trehalose and inulin.

[0018] Preferably, in the preparation of the MD-TA-IN microcapsule powder, the inlet temperature of the spray drying is 140°C-150°C, and the outlet temperature of the spray drying is 60°C-70°C.

[0019] The plant-based milk microcapsules containing walnut oil are prepared by the method for preparing the plant-based milk microcapsules containing walnut oil as described above.

[0020] Preferably, the water content of the plant-based milk microcapsules containing walnut oil is 2.46±0.64%.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention provides a method for preparing plant-based milk microcapsules containing walnut oil. The method comprises the following steps: first preparing SPI-Cur-NPs powder, then preparing an emulsion, preparing the emulsion and walnut oil into a nanoemulsion, and finally mixing maltodextrin (MD), anhydrous trehalose (TA) and inulin (IN) as a mixed wall material system, and preparing plant-based milk microcapsules encapsulating walnut oil by spray drying. The preparation method is simple; the combination of anhydrous trehalose and maltodextrin can reduce the fracture formation of particles containing only maltodextrin, and the prepared microcapsule powder forms a stronger intermolecular hydrogen bond network and an obvious amorphous structure, enhances the integrity of the wall, thereby reducing particle collapse, and significantly improves the encapsulation rate (92.7%) and solubility (>95%); and curcumin and the composite wall material form a dense and uniform coating layer, which provides an effective physical barrier, so that the microcapsule powder has excellent oxidative stability; and the prepared microcapsule powder has a long storage time, the quality of the oil will not be reduced, and the transportation efficiency is improved.

[0023] In addition, the present invention uses anhydrous Quhatang as the composite wall material. The anhydrous trehalose does not contain crystal water, has more stable physical and chemical properties, and exhibits better embedding effect in the microencapsulation process; at the same time, the solubility and thermal stability of the anhydrous trehalose are also better, which is conducive to spray drying; and the anhydrous trehalose has excellent glass transition characteristics, which can effectively protect the embedded substances, especially in the high-temperature processing process, it can better maintain the product stability; secondly, the anhydrous trehalose has strong antioxidant properties and low hygroscopicity, which can improve the storage stability of the microcapsule; thirdly, its good interfacial activity and emulsification properties are conducive to forming a uniform and stable microcapsule structure; finally, the anhydrous trehalose has high solubility and good biocompatibility, which is conducive to the preparation of microcapsules, so that its embedding efficiency and product stability are good.

[0024] Moreover, the encapsulated walnut oil of the present invention contains omega-3 fatty acids (especially α-linolenic acid) and the ratio of oleic acid to linoleic acid is also better, which makes the microencapsulated walnut oil product more effective in promoting brain development and improving cardiovascular function; in addition, the unique nutty aroma and high vitamin E content of walnut oil also bring additional flavor and antioxidant advantages to the microcapsules.

[0025] In addition, the microcapsule powder can well protect the active ingredients in walnut oil, improve its stability and bioavailability, and make the product easier to be absorbed and utilized by the human body; finally, the microcapsule powder has better dispersibility and ease of application, and is particularly suitable for addition to various functional foods and nutritional supplements. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1SEM images of different microcapsule systems: control group, SPI-cur-NPs, MD and MD-TA-IN, with magnifications of 2000x and 5000x, respectively.

[0027] Figure 2 Characterization of microencapsulation systems: (A, B) Fourier transform infrared spectra, (C) X-ray diffraction patterns, and (D) DSC thermograms of different compositions and formulations.

[0028] Figure 3 Changes in oxidation indexes and kinetic analysis of walnut oil microcapsules with different wall materials during accelerated storage at 60°C. (A) Peroxide value (PV); (B) TBARS value; (C) Zero-order kinetics of lipid oxidation; (D) First-order kinetics of lipid oxidation.

[0029] Figure 4 The visual appearance of walnut oil microcapsule powder with different wall materials at different water activities (aw). SC: control sample with soy protein-curcumin nanoparticles as wall material; MD: maltodextrin as wall material; MD-TA-IN: composite wall material composed of maltodextrin, anhydrous trehalose and inulin. DETAILED DESCRIPTION

[0030] The technical solutions and technical effects of the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings of the present invention.

[0031] 1. Preparation:

[0032] Example 1: (MD-TA-IN group)

[0033] Materials: Maltodextrin (>95%) and inulin (>90%) were purchased from Sora Biotechnology Co., Ltd. (Beijing, China), and the remaining reagents were of analytical grade without further purification.

[0034] Preparation of soy protein isolate (SPI): Soybean meal (60 g) was dispersed in distilled water with a solvent / solid ratio of 15 / 1 (w / v), stirred continuously at 25°C for 2 hours, and then the pH of the dispersion was adjusted to 8.0 with 0.5M NaOH, and then centrifuged at 7618xg for 30 minutes. The obtained supernatant was adjusted to the isoelectric point (pH = 4.5) with 2M HCl and allowed to settle for 1 hour. The precipitate was collected and further centrifuged at 6500xg for 20 minutes (at 4°C). The centrifuged precipitate was rinsed twice with distilled water, then dissolved in distilled water, and the pH was adjusted to 7.5 with 2M NaOH. After complete dissolution, it was placed in a dialysis bag and dialyzed for 48 hours, frozen at -80°C and freeze-dried for standby use. The powder formed was soy protein isolate (SPI), and the SPI stock solution (2wt%) was prepared by dispersing the freeze-dried SPI in distilled water.

[0035] Preparation of SPI-Cur-NPs powder: Heat a 2wt% SPI solution in a water bath at 95°C for 15 minutes and store at 4°C overnight. Heat the SPI stock solution in a water bath at 95°C for 15 minutes, then quickly cool to room temperature in an ice bath, and gradually add 4.5mg / ml curcumin-ethanol solution to a concentration of 50μmol / L. After reacting for 8 hours in the dark, centrifuge at 4000rpm for 5 minutes to remove unreacted curcumin. The excess ethanol in the supernatant was evaporated at 45°C using a rotary evaporator, and then freeze-dried to obtain SPI-Cur-NPs powder.

[0036] Preparation of nanoemulsion: A certain amount of SPI-Cur-NPs was accurately weighed and dispersed in deionized water to make SPI-Cur-NPs 4%. 4wt% SPI-Cur-NPs powder was dissolved in deionized water and stirred at ambient temperature for 2 hours, and then incubated at 4°C overnight to ensure complete hydration. To prepare the emulsion, the SPI solution was mixed with walnut oil in a ratio of 9:1 (v:v) and homogenized at 13000rpm for 3 minutes to obtain a micron-sized emulsion. The micron-sized emulsion was further treated with an ultra-high pressure homogenizer at 100 MPa at 4°C for three cycles to produce a nanoemulsion.

[0037] Preparation of MD-TA-IN microcapsule powder: The nanoemulsion was mixed with an equal volume of 30% wall material solution (maltodextrin or a 1:1:1 mixture of maltodextrin, anhydrous trehalose and inulin), and then sheared and homogenized at 12000rpm for 1 minute. Finally, the mixture was sent to a B290 spray dryer by a peristaltic pump for spray drying (inlet temperature 145±5℃, outlet temperature 65±5℃, fan flow rate 35L / min). The dried microcapsule powder was collected in a polyethylene bag and stored in a light-proof closed desiccator before analysis.

[0038] Comparative Example 1: (Blank Group)

[0039] The preparation of soy protein isolate (SPI) was the same as in Example 1;

[0040] Preparation of nanoemulsion: Accurately weigh a certain amount of SPI and disperse it in deionized water to make SPI 4%. Stir at room temperature for 2 hours, and then place in a refrigerator at 4°C for hydration overnight. Add 10% MCT (W / W) by volume to the aqueous phase, and homogenize it at 13000rpm for 3min using a high-speed homogenizer to obtain a micron-sized emulsion. Subsequently, at 4°C, use an ultra-high pressure homogenizer at a pressure of 100MPa to cycle the micron-sized emulsion for 3 times to obtain a nanoemulsion. In addition, during the homogenization process, keep an ice bath to control the sample temperature.

[0041] Preparation of microcapsule powder: The nanoemulsion was sent into a B290 spray dryer by a peristaltic pump for spray drying (inlet temperature 145±5°C, outlet temperature 65±5°C, fan flow rate 35L / min). The dried microcapsule powder was collected in a polyethylene bag (recorded as a blank control) and stored in a light-proof sealed desiccator before analysis.

[0042] Comparative Example 2: (SPI-Cur-NPs group)

[0043] The preparation of soy protein isolate (SPI), the preparation of SPI-Cur-NPs powder, and the preparation of nanoemulsion were the same as in Example 1;

[0044] Preparation of SC microcapsule powder: The nanoemulsion was sent into a B290 spray dryer by a peristaltic pump for spray drying (inlet temperature 145±5°C, outlet temperature 65±5°C, fan flow rate 35L / min). The dried microcapsule powder was collected in a polyethylene bag and stored in a light-proof sealed desiccator before analysis.

[0045] Comparative Example 3: (MD Group)

[0046] The preparation of soy protein isolate (SPI), the preparation of SPI-Cur-NPs powder, and the preparation of nanoemulsion were the same as in Example 1;

[0047] Preparation of MD microcapsule powder: The nanoemulsion was mixed with an equal volume of 30% maltodextrin (w / v) wall material solution, and then sheared and homogenized at 12000rpm for 1 minute. Finally, the mixture was sent to a B290 spray dryer through a peristaltic pump for spray drying (inlet temperature 145±5℃, outlet temperature 65±5℃, fan flow rate 35L / min). The dried microcapsule powder was collected in a polyethylene bag and stored in a light-proof sealed desiccator before analysis.

[0048] 2: The nanoemulsions and microcapsule powders prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were characterized.

[0049] 2.1 Particle size and viscosity of nanoemulsion before spray drying

[0050] The viscosity and average particle size of the mixture before spray drying were measured using a DHR-3 rheometer and a Malvern-3000, respectively, with the shear rate set at 0.1-100 s. -1 The particle size and viscosity test results of the nanoemulsions obtained in Example 1, Comparative Examples 2 and 3 are shown in Table 1.

[0051] Table 1

[0052]

[0053] As shown in Table 1, the viscosity of the SC nanoemulsion is 1.4±0.1mPa-s. After adding the wall material, the viscosity of the emulsion gradually increased, reaching a maximum of 8.1±0.6mPa-s. However, the nanoemulsion with the added wall material still maintains the Newtonian fluid properties (flow property index n=1) to ensure the best rheological properties and atomization efficiency during the spray drying process. And the average particle size of the nanoemulsion droplets is always maintained at about 245nm, no matter what kind of wall material is added or what kind of component is changed, there is no significant difference (P<0.05), and the MD, TA and IN added by the present invention are all inert and neutral materials, which will not produce obvious interactions with the emulsifier, nor change the interfacial tension, so that the particle size consistency is good, which can promote the formation of microcapsules with uniform particle size distribution and improve the solubility of the powder.

[0054] 2.2 Water content, solubility and wettability of microcapsules

[0055] A certain amount of the microcapsules prepared in Example 1 and Comparative Examples 1 to 3 were weighed and placed in an oven until a constant weight was reached. The water content (%) was calculated based on the weight difference before and after drying.

[0056] Accurately weigh one gram of powder of the microcapsules prepared in Example 1 and Comparative Examples 1 to 3, and disperse them in 100 ml of distilled water. Record the time required for all the powders to be completely wetted without stirring.

[0057] Accurately weigh 0.5 g of powder sample, dissolve in 10 ml of distilled water, and stir for 3 minutes. Then transfer the solution to a centrifuge tube and centrifuge at 1500 rpm and 4°C for 20 minutes. Transfer all supernatant to a petri dish and dry in an oven to constant weight. Calculate the solubility of the powder in cold water based on the weight after drying. Obtain the data in Table 2.

[0058] Table 2

[0059]

[0060] The moisture content of microcapsule powder is an important indicator for evaluating the storage capacity of microcapsule products. The lower the moisture content, the longer the shelf life. As shown in Table 2, the moisture content of the blank group and the MD-TA-IN group was only 2.46±0.64%, which was significantly lower than 6.47±0.24% of the maltodextrin group; the powder dissolution time of the blank group lacking wall material protection exceeded 3 hours, and the solubility was only 10.78%; the solubility and wettability of the microcapsules with added wall materials were significantly improved; although maltodextrin has strong hygroscopicity, the dissolution time of the microcapsule powder using pure maltodextrin as the wall material was 32.81±2.41 minutes, and the solubility was 79.72±0.85%. The microcapsules prepared using MD-TA-IN (MD, TA and inulin) showed significant improvements in dissolution time and solubility (P<0.05), with the dissolution time shortened to 8.49±0.51 minutes and the solubility increased to 96.4±2.2%, because inulin and maltodextrin formed intermolecular hydrogen bonds, which further improved the water solubility of the microcapsules.

[0061] 2.3 Microcapsule bulk density and surface oil content

[0062] The volume density of the microcapsule is determined by measuring the ratio of the volume occupied by the powder in the cylinder to the mass. The microcapsule powders prepared in Example 1 and Comparative Examples 1 to 3 are slowly added to a 5 ml measuring cylinder until the 5 ml mark is reached. The weight of the added powder is measured to calculate the volume density in g / ml.

[0063] Accurately weigh 1 gram of microcapsule powder, mix it with 10 ml of petroleum ether (30°C-60°C) in a 10 ml volumetric flask, stir it manually and filter it. Rinse the volumetric flask and glass rod three times with petroleum ether. Mix all the used petroleum ether in a flask, heat it in an oven and dry it to constant weight to obtain the data in Table 2.

[0064] As shown in Table 2, the volume densities of microcapsule powders prepared using MD and MD, TA, IN were 0.48 g / ml and 0.632 g / ml, respectively, with significant differences (P<0.05). The microcapsules prepared using MD, TA, IN may be much smaller than those prepared using MD. The mixture of MD, TA, IN as wall materials will accelerate the formation of the microcapsule particle shell during the spray drying process, making the particles smaller and more uniform. The intermolecular hydrogen bonds between inulin and maltodextrin enhance the structural stability of the wall material, which helps to form a denser particle structure and increase the volume density.

[0065] After adding the wall material, all the spray-dried powders showed higher encapsulation efficiency and lower surface oil content. The data in Table 2 show that the surface oil content of the microcapsules prepared with pure maltodextrin is slightly higher, which may be caused by the inevitable wrinkles or cracks on the powder surface. Compared with the smooth powder surface, the solvent can often extract more oil droplets from these wrinkled or cracked powder surfaces. In the present invention, the addition of inulin as the wall material accelerates the formation of the microcapsule particle shell, thereby hindering the diffusion of oil droplets to the powder surface.

[0066] 2.4 Microcapsule microstructure

[0067] The microstructure of different microcapsules was observed by scanning electron microscopy (SEM, Zeiss Sigma 300, Germany). The acceleration voltage was set to 15 kV, and images were taken at 2000 times and 5000 times magnifications. Figure 1 The scanning electron microscope image shown. Figure 1 As shown, the blank group (control) lacks additional wall material and exhibits obvious wrinkles, which may be due to the fact that the film formed by SPI during the drying process is not strong enough to withstand the surface tension changes caused by water evaporation; on the contrary, no obvious wrinkles were observed on the surface of the powder particles of the two microcapsules containing added wall materials; this indicates that the wall material used in the manufacture of these microcapsules has excellent molecular flexibility, thereby enhancing the film-forming ability of the tiny droplets during the drying stage and inhibiting the formation of wrinkles, and the SPI-Cur-NPs used in this application have excellent emulsification and film-forming properties, so that the microcapsules can remain intact despite the addition of only maltodextrin; and the number of surface cracks on the powder prepared by the mixed sugar is significantly less than that of the powder prepared using only maltodextrin, because anhydrous trehalose provides a stronger surface structure, and the combination of anhydrous trehalose and maltodextrin can reduce the fracture formation of particles containing only maltodextrin and enhance the integrity of the wall, thereby reducing particle collapse, which is conducive to better sealing of the microcapsules and providing better protection for the core material,

[0068] 2.5 Fourier transform infrared spectroscopy

[0069] 2 mg of different microcapsule samples were accurately weighed, mixed with 200 mg of KBr, fully ground in an agate mortar, and pressed into granules. The measurements were performed using a Fourier transform spectrophotometer (Nicolet IS10, USA) at 25 °C. The scanning range was set to 400-4000 cm -1 , the instrument resolution is 4cm -1 The number of scans was set to 64. A background spectrum was collected before the sample measurement.

[0070] like Figure 2 As shown in B, all microcapsule samples have a peak at 1740 cm -1A new absorption peak appeared near the SPI and SPI-Cur-NPs groups, which may be due to the C=O stretching vibration of the fatty acid ester group in walnut oil, confirming the successful encapsulation of the core material. The Fourier transform infrared spectra of the SPI and SPI-Cur-NPs groups were at 1650 cm -1 and 1540cm -1 The typical amide I and amide II bands are shown nearby, and there are no new characteristic peaks due to the dominant non-covalent interaction between SPI and curcumin; however, the peak shape and intensity of the SPI-Cur-NPs group in these two regions change slightly. This phenomenon can be attributed to the fact that curcumin changes the thermal stability of SPI-Cur-NPs, thereby reducing the degree of denaturation of SPI during high-temperature spray drying.

[0071] Further analysis of the Fourier transform infrared spectrum revealed more information about the composition of the microcapsules. After adding MD as the wall material, the microcapsules -1 A broad -OH stretching vibration peak appeared near the 1000-1200 cm-1 region, and a characteristic CO stretching vibration peak appeared in the 1000-1200 cm-1 region. Figure 2 The MD characteristic peaks in the MD-TA-IN group were consistent with those in the MD group shown in A. Compared with the MD group, the MD-TA-IN group showed a -1 The peak shape in the region is more complex, reflecting the interaction between various sugar molecules. -1 The -OH peak nearby is broader and stronger. This enhancement of intermolecular interaction may be due to the large number of hydroxyl groups in inulin molecules, which can form multiple hydrogen bonds with other sugar molecules. It is worth noting that the MD-TA-IN group has a strong peak at 1740 cm -1 The intensity of the characteristic peaks near is consistently higher than that of all other experimental groups, indicating that the MD-TA-IN group encapsulated more walnut oil.

[0072] The formation of an amorphous structure enhances the flexibility of the wall material, which is beneficial to establishing a continuous encapsulation layer for the microcapsules, reducing surface defects of the wall material, reducing internal stress, and thus reducing the degree of microcapsule rupture.

[0073] 2.6DSC

[0074] The crystal structure of the microcapsule sample was determined using an X-ray diffractometer (Shimadzu XRD-6100, Japan). A Cu Kα1 radiation source (λ=0.15406 nm) was used. The scanning speed was set to 1° / min, the step length was 0.2°, and the acquisition range was 5°-50°.

[0075] like Figure 2As shown in Figure D, the SPI sample exhibits an obvious endothermic peak at around 150°C, corresponding to the thermal denaturation process of the protein. In contrast, the curve of the SPI-Cur-NPs sample is relatively smooth, without an obvious endothermic peak, indicating that the presence of curcumin may enhance the thermal stability of the microcapsules. The MD sample exhibits a slight endothermic transition at approximately 130°C, which may correspond to its glass transition temperature (Tg). It is worth noting that the DSC curve of the MD-TA-IN sample is the smoothest, with no obvious thermal transition within the tested temperature range, indicating that the mixed sugar system forms a more stable amorphous structure, which may have a wider glass transition range or higher thermal stability.

[0076] Importantly, none of the microcapsule samples showed a distinct thermal transition associated with pure walnut oil over the entire temperature range tested. The absence of such a transition strongly suggests that the core material (walnut oil) was successfully encapsulated in the microcapsules, forming a homogeneous composite system with the wall material. The results show that the hybrid sugar wall material has unique thermal properties, including a more stable amorphous structure and excellent thermal stability, which makes the prepared MD-TA-IN microcapsules have excellent encapsulation efficiency, storage stability and antioxidant properties.

[0077] 2.7 Oxidative stability of microcapsules

[0078] Accelerated oxidation tests were used to evaluate the oxidative stability of the microcapsules. According to the Van't Hoff empirical formula, storage at 60°C for 18 days is equivalent to storage at 20°C for approximately 288 days (Lima, Gomes, & Tran, 2020). Figure 3 As shown in the figure, the oxidation level of the SPI-Cur-NPs group was significantly lower than that of the control group, which may be related to the addition of curcumin. After adding the polysaccharide wall material, the antioxidant activity of the microcapsules was further enhanced, among which the oxidative stability of the MD-TA-IN group was the most outstanding. The PV value and TBARS value of the MD-TA-IN group were 2.21mmol / kg and 97.8μg / g, respectively, which were 34.4% and 18.7% lower than those of the blank group, respectively.

[0079] The results showed that both the zero-order and first-order kinetic models could well describe the oxidation process of all samples (R2≥0.94), with the zero-order model fitting slightly better. This suggests that the oxidation reaction of microencapsulated oils often follows zero-order kinetics, which may be due to the protective effect of the microcapsule wall material, making oxygen diffusion the rate-limiting step. Kinetic analysis further confirmed the superiority of the MD-TA-IN group, whose zero-order reaction slope was 0.1528, significantly lower than that of the control group (0.2356) and other microcapsule formulations (SPI-Cur-NPs: 0.1861, MD: 0.1727). Based on these data and referring to the European Food Codex regulations on PV values ​​in vegetable oils (PV≤10mmol / kg), we conducted a quantitative assessment. The results showed that under accelerated oxidation conditions at 60°C, the storage period of the control group was 33 days, while the storage period of the MD-TA-IN microcapsules could be as long as 64.35 days. When these results are converted to storage at room temperature of 20°C, the theoretical storage period of the blank group is 528 days (about 17.6 months), while the theoretical storage period of the MD-TA-IN group microcapsules can reach 1030 days (about 34.3 months). This result shows that under the temperature of 20°C, the storage period of the MD-TA-IN group microcapsules is significantly extended by 95.1% compared with the control group, which directly reflects the excellent effect of the MD-TA-IN group microcapsules in delaying the oxidation of the core material. It shows that the composite wall material forms a stronger intermolecular hydrogen bond network and a more obvious amorphous structure, thus forming a dense and uniform coating layer, which plays an effective physical barrier role; and this structure can also capture free radicals through the hydroxyl groups of polysaccharides, thereby slowing down the oxidation process.

[0080] 2.8 Hygroscopic properties of microcapsules

[0081] Figure 4 The morphology of the microcapsule samples after storage at different humidity levels is shown. The storage weight of the SPI-Cur-NPs group did not change significantly at all humidity levels, indicating that the sample was almost completely non-hygroscopic; when polysaccharides were added as wall materials, the microcapsules based on SPI-Cur-NPs showed hygroscopicity and displayed significant inter-particle adhesion at higher water activity levels; this was mainly due to the formation of intermolecular hydrogen bonds between polysaccharides and water molecules, which increased the sensitivity of the microcapsules to environmental humidity.

[0082] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing plant-based milk microcapsules containing walnut oil, characterized in that: The following steps are involved: Preparation of SPI-Cur-NPs powder: heat the soy protein isolate in a water bath, then cool to room temperature, add curcumin-ethanol solution, react for 7-9 hours, centrifuge, rotary evaporate, and freeze-dry to obtain SPI-Cur-NPs powder; Preparation of nanoemulsion: S1: SPI-Cur-NPs powder was dissolved in deionized water, stirred for 2 h, and incubated at 4 °C overnight to obtain SPI emulsion; S2: mixing the SPI emulsion and walnut oil in a predetermined volume ratio, and then uniformly obtaining a microemulsion; S3: homogenizing the microemulsion to obtain a nanoemulsion; Preparation of MD-TA-IN microcapsule powder: The nanoemulsion is mixed and homogenized with an equal volume of a composite wall material solution to obtain a mixture, and the mixture is spray-dried to obtain microcapsule powder.

2. The method for preparing plant-based milk microcapsules containing walnut oil as claimed in claim 1, characterized in that: In the preparation of the SPI-Cur-NPs powder, the concentration of the curcumin-ethanol solution is 4.3-4.7 mg / mL, and the concentration of the solution reaches 50 μmol / L after the curcumin-ethanol solution is added.

3. The method for preparing plant-based milk microcapsules containing walnut oil as claimed in claim 1, characterized in that: In the step S2, the volume ratio of the SPI emulsion to the walnut oil is 9:

1.

4. The method for preparing plant-based milk microcapsules containing walnut oil as claimed in claim 1, characterized in that: In the step S3, the average particle size of the nanoemulsion droplets is 243nm-247nm.

5. The method for preparing plant-based milk microcapsules containing walnut oil as claimed in claim 1, characterized in that: In the step S3, the viscosity of the nanoemulsion is below 8.1±0.6 mPa-s.

6. The method for preparing plant-based milk microcapsules containing walnut oil as claimed in claim 1, characterized in that: In the preparation of the MD-TA-IN microcapsule powder, the composite wall material solution is maltodextrin or a 1:1:1 mixture of maltodextrin, anhydrous trehalose and inulin.

7. The method for preparing plant-based milk microcapsules containing walnut oil as claimed in claim 1, characterized in that: In the preparation of the MD-TA-IN microcapsule powder, the inlet temperature of the spray drying is 140°C-150°C, and the outlet temperature of the spray drying is 60°C-70°C.

8. Plant-based milk microcapsules containing walnut oil prepared by the method for preparing plant-based milk microcapsules containing walnut oil as described in any one of claims 1 to 7.

9. The plant-based milk microcapsules containing walnut oil according to claim 8, characterized in that: The water content of the plant-based milk microcapsules containing walnut oil is 2.46±0.64%.